2018
DOI: 10.5625/lar.2018.34.3.111
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Pycnogenol®, a pine bark extract, in a rat model of testosterone propionate-induced benign prostatic hyperplasia

Abstract: Benign prostate hyperplasia (BPH) is a male reproductive disease that has gained increasing importance in recent years. The present study investigated whether Pycnogenol® (PYC), a standardized French maritime pine bark extract, could prevent BPH induced by testosterone propionate (TP) in rats. Male Sprague-Dawley rats were randomly divided into five groups of six rats. One group was used as a normal control rats and the other groups received subcutaneous injections of TP for 4 weeks to induce BPH. In the two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…This result is supported by histological analysis of prostate, which is based on The administration of PBE led to the marked decline in the PCNA and Ki-67 expressions on the prostate. PCNA and Ki-67 are well-known as important indicators of cellular proliferation (Ko et al, 2018) and their expression levels are elevated in the prostate of BPH animals (Romar et al, 2016). The levels of these proteins are correlated with the proliferative function of various cells, which makes them valuable markers in the diagnosis of BPH and for evaluating the efficacy of test materials against BPH (Rho et al, 2019;Zhong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result is supported by histological analysis of prostate, which is based on The administration of PBE led to the marked decline in the PCNA and Ki-67 expressions on the prostate. PCNA and Ki-67 are well-known as important indicators of cellular proliferation (Ko et al, 2018) and their expression levels are elevated in the prostate of BPH animals (Romar et al, 2016). The levels of these proteins are correlated with the proliferative function of various cells, which makes them valuable markers in the diagnosis of BPH and for evaluating the efficacy of test materials against BPH (Rho et al, 2019;Zhong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Androgens such as testosterone and DHT are crucial mediators in the growth of stromal and epithelial cell of the prostate during BPH progression (Rho et al., 2019 ). They bind to androgen receptors and activate the transcription of growth factors, resulting in the growth of stromal and epithelial cells of the prostate (Ko et al., 2018 ). Particularly, DHT, a metabolite of testosterone, is converted by 5α‐reductase and has 10 times more affinity for androgen receptors than testosterone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results indicated that Pycnogenol ® inhibits the development of BPH and that this is closely associated with a reduction in DHT levels. [ 91 ] ( Table 2 ).…”
Section: Medicinal Plants Widely Used In the Treatment Of Bphmentioning
confidence: 99%